Analysis of Moral Value in the Picture Story of the Fable Edition “Our Tax” by the Directorate Of Extension, Services, and Public Relations - Rianti; Septiana Pradyta; Trisnawati Hutagalung; Fania Nurtriana, Fania Nurtriana (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
The purpose of this study is to describe the moral values ​​contained in the fable book "Our Taxes". The type of research used is descriptive qualitative. The source of data in this study is the entire text contained in the fable book. In this study, the researcher used Sulistyorini's theory of moral values ​​as the basis for the moral values ​​to be studied. Based on the results of the analysis of moral values ​​in the fable story book "Our Taxes" contains several moral values ​​that deserve to be imitated. The first story with the title "The Bee King and a Spoon of Wisdom" contains obedience, courage, honesty, fairness, keeping promises, being careful in acting, acting, and harmony. The second story with the title “The Dog and the Rabbit” finds obedience, courage, honesty, fairness, wisdom, keeping promises, good character, careful in acting, likes to help, harmony, and likes to give advice. While the third story with the title "Ants and Crickets" was found to contain the values ​​of hard work, discipline, responsibility, independence, cooperation, and help. Thus, the existence of moral values ​​contained in the fable is very useful for readers, especially among children. In addition, the moral values ​​contained in fable stories can also overcome the moral crisis, because children's literature can provide opportunities for children as readers for moral sources.